Variation in rhizosphere microbiota correlates with edaphic factor in an abandoned antimony tailing dump. (October 2019) - Xiao, Enzong; Ning, Zengping; Xiao, Tangfu; Sun, Weimin; Qiu, Yaqun; Zhang, Yu; Chen, Jieyi; Gou, Zilun; Chen, Yuxiao
Abstract: The distribution pattern of root-associated bacteria in native plant growth in tailing dumps with extreme conditions remains poorly understood and largely unexplored. Herein we chose a native plant, Bidens bipinnata, growing on both an Sb tailing dump (WKA) and adjacent normal soils (WKC) to in-depth understand the distribution pattern of root-associated bacteria and their responses on environmental factors. We found that the rhizosphere microbial diversity indices in the tailing dump were significantly different from that in the adjacent soil, and that such variation was significantly related with soil nutrients (TC, TOC, TN) and metal(loid) concentrations (Sb and As). Some dominant genera were significant enriched in WKA, suggesting their adaption to harsh environments. Notably, these genera are proposed to be involved in nutrient and metal(liod) cycling, such as nitrogen fixing ( Devosia, Cellvibrio, Lysobacter, and Cohnella ), P solubilizing ( Flavobacterium ), and Sb and As oxidation ( Paenibacillus, Bacillus, Pseudomonas, and Thiobacillus ). Our results suggest that certain root-associated bacteria in tailing dump were governed by soil edaphic factors and play important ecological roles in nutrient amendments and metal cycling for the successful colonization of Bidens bipinnata in this tailing dump. Graphical abstract: Image 1 Highlights: Bidens bipinnata was chosen to study the distribution pattern of rhizosphere microbiota in Sb tailing dump. Rhizosphere microbiota in tailing dump was significantly related with soil nutrients and metal(loid)s concentrations. The dominant rhizosphere genera are involved in nitrogen fixation, P solubilization, and Sb/As oxidation in tailing dump. Abstract : Rhizosphere microbiota was governed by soil edaphic factors and play important roles in nutrient amendments and metal cycling for Bidens bipinnata in tailing dump.